EFFECT OF INFORMATION AND COMMUNICATION TECHNOLOGY ON PROCUREMENT PERFORMANCE IN KENYA - MBURU, DAVID KIARIE; MWANGI, PETER (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Information and Communication Technology (ICT) in procurement is the automation of processes, controls, and information production using computers, telecommunications, software and other gadgets that ensure smooth and efficient running of procurement activities. Private and public sector organizations have been utilizing IT systems to streamline and automate their purchasing and other processes over the past years. It is only in the past decade that ICT systems have attracted attention. Apart from offering accommodation and various hospitality services, it encourages the inflow of tourists from other parts of the world thereby boosting our economy in the tourism industry. This study fills a gap that existed in the previous knowledge, in these areas of research whereby many studies have not exploited the effect of information and communication technology in procurement performance in star rated hotels. The researcher addressed the effect of information and communication technology in procurement performance in star rated hotels. The review indicates that a number of independent variables exist and have been adequately not been studied by past researchers. The study tries to bring these variables into the limelight in order to fill the existing gaps.